Audit Operasional Pada PT BPR Puridana Arthamas Untuk Mengetahui Efektivitas Dan Kinerja Karyawan - Mei Nurlinda; Hwihanus Hwihanus (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to provide knowledge about employee performance in determining effectiveness as well as making recommendations and suggestions based on the results of the operational audit of PT BPR Puridana Arthamas. The research was carried out using a qualitative descriptive method by carrying out data collection, literature review, interviews and questionnaires on HRD. Data analysis uses qualitative by conducting an audit of the human resource planning process, recruitment, selection, orientation, placement, compensation and bonuses. Based on the results of audits that have been carried out, HR or employee management activities have been carried out effectively.